MEMBANGUN HEALTH-PRENEURSHIP BAGI MAHASISWA KEDOKTERAN DAN KEDOKTERAN GIGI UNIVERSITAS HANG TUAH SURABAYA - Ghita Hadi Hollanda; Indarti; Edi Pratiknya D (Jurnal Pengabdian Masyarakat Pesisir, 2022)
The introduction of entrepreneurship is expected to change the mindset of students to aspire to become entrepreneurs, not just ambitions to become Civil Servants (PNS). This understanding must be started while still a student. Entrepreneurship education is beneficial in providing provisions before medical faculty and dentistry faculty students will later become doctors or dentists. This entrepreneurship development program can be implemented as a "Building health-preneurship" workshop. The method of implementing the training to build health-preneurship in 3 ways, namely a. provision of materials and discussions with experts; b. visits and discussions with health-preneurship actors; c. participants' exposure to the business model canvas. The results of the health-preneurship-building activities showed a significant difference between the participants' pre-test and post-test results. The difference in these results indicates an increase in the knowledge gained by the participants